Advective Displacement Method for the Characterisation of Pore Water Chemistry and Transport Properties in Claystone. (14th January 2018) - Mäder, Urs
Abstract : The advective displacement method applies large hydraulic gradients to a confined rock core sample to yield small aliquots of the preserved in situ pore water, applicable to aquitard rocks with hydraulic conductivities as low as 10 −14 m/s. Examples from argillaceous rocks indicate that only minor artefacts are induced and that analytical methods optimized for small aliquots provide a comprehensive chemical and isotopic characterisation. Multicomponent transport properties are derived from extending experimental time and using a traced artificial pore water for injection. Examples include quantification of the anion exclusion effect that can even resolve a small difference between transport properties for chloride and bromide in claystone. Controls by mineral saturation and cation exchange processes are also constrained by data from this approach. Technical details are provided for construction, material selection, components, sensors, and analytical issues.